Long term functional outcome for the cubital tunnel syndrome after endoscopic assisted release of the ulnar nerve: research - Spies, Christian; Cavalcanti Kußmaul, Adrian; Heinz, M.; Bruckner, Thomas; Müller, Lars Peter; Unglaub, Frank; Ayache, Ali (Archives of orthopaedic and trauma surgery, 2024)
The endoscopic assisted release for cubital tunnel syndrome (CuTS) gained popularity in recent years with unclear long-term results. This study aims to evaluate long term results regarding functional and subjective outcomes after endoscopic assisted release for the CuTS.